The effect of Environmental Social and Governance (ESG) rating and profitability on dividend policy: Evidence from commercial banks - Keukeu Firda Lestari; Rima Rachmawati (WIM Solusi Prima, 2026)
Dividend policy is one of the factors that attracts considerable attention from investors. The existing phenomenon indicates that dividend policy, as measured by the Dividend Payout Ratio (DPR), tends to increase despite the restrictions on dividend distributions imposed by the Otoritas Jasa Keuangan (OJK). In addition, profitability, as measured by Return on Equity (ROE), tends to decline, while Environmental Social and Governance (ESG) rating exhibit fluctuating movements. These conditions suggest a discrepancy between empirical evidence and theoretical expectations, which posit that both factors serve as important determinants of dividend policy. This study aims to analyze the effects of Environmental Social and Governance (ESG) rating and profitability on dividend policy in commercial banks listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. This research employs a descriptive and associative research design with a quantitative approach. The data used in this study consist of secondary data obtained from annual reports and ESG rating reports of commercial banks listed on the Indonesia Stock Exchange (IDX). The population comprises all commercial banks listed on the IDX, with a sample of 16 commercial banks selected through purposive sampling over a three-year observation period. The analytical technique applied is panel data regression using EViews 13 software, while hypothesis testing is conducted using the partial hypothesis test (t-test). The results reveal that Environmental Social and Governance (ESG) rating has a positive effect on dividend policy, and profitability also has a positive effect on dividend policy. These findings indicate that improvements in ESG rating and profitability are likely to be accompanied by higher dividend distributions.